Penerapan Metode Pembelajaran Berbasis Proyek Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematika Di Sekolah Menengah - Devi Anggi Oktaviani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The application of Project Based Learning (PBL) Methods has become the main research objective in improving mathematical problem solving abilities in secondary schools. This article was written with the aim of exploring the effectiveness of Project Based Learning (PBL) in the context of mathematics learning. The research method used is literature study and comprehensive analysis of related research results. The research results show that PBL makes a positive contribution in improving students' mathematical problem solving abilities. The factors of active student involvement, development of collaborative skills, and application of mathematical concepts in real world contexts are the keys to the success of PBL. The practical implication of these findings is the need for integration of PBL in secondary school mathematics curricula to support the development of better problem solving abilities.